AN ANALYSIS OF STUDENTS’ GRAMMATICAL ERROR IN WRITING PERSONAL LETTER - Dewi - Sartika; Inka Sundari; Ratna Nery (IAIN Syekh Nurjati Cirebon, 2021)
This study aimed to find out grammatical errors in writing personal letter and the most grammatical errors made by the eleventh graders of SMA Negeri 5 Ogan Komering Ilir. This study used descriptive qualitative research method. The subject of the study was the eleventh social one students of SMA Negeri 5 Ogan Komering Ilir in the academic year of 2020/2021. The technique of collecting the data were a writing testusing google form. To check the validity and reliability of the test, a triangulation method was applied. The information was presented in a descriptive manner and assessed using a percentage calculation. The calculations presented that the students made 12.5% sentence pattern errors, 24.1% tense errors, 9.17%pronoun errors, 2.5% preposition errors, 20% punctuation errors, and 31.66% spelling errors.The most dominant of grammatical errors made by students was error of spelling (31.66%).